THE EFFECT OF THE READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE LEARNING MODEL BASED ON AN STEM APPROACH ASSISTED BY AUTOGRAPH ORIENTED TO STUDENTS' MATHEMATICAL LITERACY ABILITY - Guslisnawati, Guslisnawati; Marsigit, Marsigit; Muliyana, Ana (PATTIMURA UNIVERSITY, 2024)
The purpose of this study was to determine whether there is an influence in the application of the STEM-based Read, Answer, Discuss, Explain, and Create (RADEC) learning model assisted by the Autograph application oriented to the mathematical literacy skills of ninth-grade students. The type of research used was Pre-Experimental with one pretest-posttest design. The population in this study was all grade IX. The approach used in this research is Science Technology Engineering and Mathematics (STEM). The research design used was pre-experimental with a one-pretest-posttest design. The sample in the study only used 1 class, namely class IXa, sampling using purposive sampling. Before being given treatment on the learning model and the ability, students were given an initial ability test (pretest), which obtained an average value of 68.23. Then, students will be given treatment in the form of learning by applying the STEM-based Read, Answer, Discuss, Explain, and Create (RADEC) learning model assisted by the Autograph application oriented to students' mathematical literacy skills. After the learning was completed, the final ability test (posttest) was given so that the posttest value was obtained with an average of 85.55. Furthermore, the -test results show that is 11.330 and at significance is 1.68, so that (11.330> 1.68), which means that is rejected and is accepted. Thus, it is obtained that there is an effect of the STEM-based Read, Answer, Discuss, Explain, and Create (RADEC) learning model assisted by the Autograph application oriented to students' mathematical literacy skills in class IXa.